Polygonum multiflorum Radix extract protects human foreskin melanocytes from oxidative stress in vitro and potentiates hair follicle pigmentation ex vivo. (27th April 2017) - Sextius, P.; Betts, R.; Benkhalifa, I.; Commo, S.; Eilstein, J.; Massironi, M.; Wang, P.; Michelet, J.‐F.; Qiu, J.; Tan, X.; Jeulin, S.
Abstract: Objective: To examine the ability of an extract from traditional Chinese medicine, Polygonum multiflorum Radix, to protect melanocyte viability from oxidative stress, a key mechanism in the initiation and progression of hair greying. Methods: To assess the antioxidant capacity of Polygonum multiflorum Radix extract, primary human foreskin melanocytes were treated with a commercially available Polygonum multiflorum Radix extract added to culture medium and exposed to hydrogen peroxide (H2 O2 ), using intracellular reactive oxygen species concentrations and glutathione/protein ratios as endpoints. To improve solubility for cosmetic uses, a new Polygonum multiflorum Radix extract was derived. As hair greying is the consequence of melanocyte disappearance in an oxidative stress environment, we checked whether the antioxidant capacity of the new Polygonum multiflorum Radix extract could preserve melanocyte viability in response to H2 O2 ‐induced oxidative stress, and preserve pigmentation within ex vivo human hair follicles. Results: In vitro treatment of primary human foreskin melanocytes with traditional available Polygonum multiflorum Radix extract resulted in decreased intracellular ROS accumulation in response to H2 O2 exposure with a concomitant preservation of glutathione‐to‐protein ratio, consistent with a protective response against H2 O2 exposure and demonstrating the promise of this extract for protecting melanocytes against oxidative stress. Melanocytes treated with the improved Polygonum multiflorum Radix extract exhibited attenuated H2 O2 ‐induced cell death, demonstrating a clear cytoprotective effect. Treatment of ex vivo human hair follicles with the improved Polygonum multiflorum Radix extract resulted in a higher level of melanin compared to vehicle‐treated controls, demonstrating an ex vivo protective effect on hair pigmentation. Conclusion: Polygonum multiflorum Radix extract protects in vitro primary human foreskin melanocytes from the deleterious effects of H2 O2 exposure and improves pigmentation within ex vivo human hair follicles, demonstrating the utility of Polygonum multiflorum Radix extract as a potential active ingredient for the protection of melanocytes against premature death. This data provides in vitro mechanistic evidence consistent with existing in vivo studies for the use of Polygonum multiflorum Radix extract as a strategy for the prevention of oxidative stress‐induced hair greying, in line with traditional Polygonum multiflorum Radix uses. Abstract : Polygonum multiflorum Radix extract protects in vitro primary human foreskin melanocytes from the deleterious effects of H2 O2 exposure and improves pigmentation within ex vivo human hair follicles, demonstrating the utility of Polygonum multiflorum Radix extract as a potential active ingredient for the protection of melanocytes against premature death. This data provides in vitro mechanistic evidence consistent with existing in vivo studies for the use of Polygonum multiflorum Radix extract as a strategy for the prevention of oxidative stress‐induced hair greying, in line with traditional Polygonum multiflorum Radix uses.